Brevipalpus mites (Acari: Tenuipalpidae): vectors of invasive, non-systemic cytoplasmic and nuclear viruses in plants - Rodrigues, Jose Carlos Verle (Springer Netherlands, 2012)
Multi-directional interactions occur among plant hosts, Brevipalpus mites and the plant viruses they transmit. Such interactions should be considered when evaluating the severity of a disease such as citrus leprosis. The current understanding of Brevipalpus-transmitted viruses relies on the capability of the vector to transmit the disease, the persistence of the virus in the host plant and the ability of the disease to spread. Previously, we discussed the Citrus leprosis virus (CiLV) and its importance and spread over the past decade into new areas of South and Central America, most recently into southern Mexico and Belize. Here, we address key questions to better understand the biology of the mite vector, fitness costs, and the peculiarities of Brevipalpus mite reproduction, virus survival, transmissibility and spread, and the expansion of the host plant range of Brevipalpus species vectoring the disease.